Validity of Module Geographic Information System-Spatial Thinking Skills (GIS-STS) - Mayalagu, Ganesan; Jaafar, Mokhtar; Kuok Choy, Lam (International Journal of Engineering and Technology, 2018)
Technological advancement in the realm of education is the process of transitioning from traditional Learning and Facilitation (L&F) to the 21st Century L&F. Geographic Information System (GIS) integration in Geography subjects is crucial in Malaysia to uphold and revive Geography subjects. Ergo, the Geographic Information System-Spatial Thinking Skills Module (GIS-STS) was developed as an intervention intended in improving the Spatial Thinking Skills (STS) and attracting students to Geography subjects. This study aims to analyze the validity of the content of the GIS-STS module. The content validity analysis utilizes the consensus assessment of seven experts. The findings exhibit that the value of the coefficient of the validity of the content is .930 and based on the sub module and the activity is .870. Hence, this proves that the GIS-STS module has a high content validity and is therefore suitable for implementation in secondary schools for Geography Form two students.Â